Effect of Mimosa pudica Extract on NF-κB Expression in Blastocystis sp. Inoculated Rats - Zirma, Dzakiyyah Nafies; Nofita, Eka; Irawati, Nuzulia; Silvia, Roza; Rahayu, Yanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Blastocystis sp. is an intestinal protozoan capable of inducing intestinal inflammation through activation of the Nuclear Factor Kappa B (NF-κB) signaling pathway. Current treatment relies on metronidazole, although its efficacy is limited by variable therapeutic responses and adverse effects. Mimosa pudica contains bioactive compounds with potential antiprotozoal and anti-inflammatory activities. This study aimed to evaluate the effect of Mimosa pudica extract on NF-κB expression in Blastocystis sp.-infected Wistar rats. An experimental post-test control group design was conducted using 30 male Wistar rats randomly assigned to six groups: negative control, positive control, metronidazole (9 mg and 13.9 mg), and Mimosa pudica extract (40 mg and 80 mg). Rats were orally inoculated with 10⁵ Blastocystis sp., followed by treatment. Phytochemical screening and FTIR was performed, and NF-κB expression was analyzed using RT-PCR. Phytochemical analysis confirmed the presence of flavonoids, alkaloids, tannins, and saponins. Administration of Mimosa pudica extract reduced NF-κB expression compared with the positive control. A significant difference in NF-κB expression was observed among the study groups (p = 0.028). These findings suggest that Mimosa pudica extract exhibits antiprotozoal and anti-inflammatory activity and may serve as a potential complementary therapy for blastocystosis through modulation of the NF-κB signaling pathway.